Integrating Product Quality Dimensions into Competitive Advantage Strategies: A Thematic Synthesis Toward Sustainable Value Creation - Haris Prawiranegar, Abdul; Adi Wijaya, Yulian (El-kahfi | Jurnal Ekonomi Islam, 2025)
This study explores how product quality dimensions can be strategically integrated into competitive advantage frameworks to create sustainable value. Despite extensive discussions on product quality and business strategy, few studies have systematically examined how quality functions within cost leadership, differentiation, and focus strategies in the digital economy era—particularly among SMEs. Using a thematic synthesis approach, this study reviews and critically analyzes academic publications from 2020–2025 obtained from Scopus, DOAJ, and Google Scholar. The findings reveal that product quality acts as a multidimensional strategic lever that connects cost efficiency, innovation-driven differentiation, and adaptive focus strategies. The study further highlights that digitalization and data-driven management systems enhance the synergy between quality, price, and promotion, enabling firms to sustain competitive advantage in volatile markets. Theoretically, this review contributes an integrative conceptual framework linking product quality to strategy typologies, while practically offering guidance for SMEs and business managers to design efficient yet value-creating quality strategies.